A lytic phage to control multidrug-resistant avian pathogenic Escherichia coli (APEC) infection - Yao, Lan; Bao, Yinli; Hu, Jiangang; Zhang, Beibei; Wang, Zhiyang; Wang, Xinyu; Guo, Weiqi; Wang, Di; Qi, Jingjing; Tian, Mingxing; Bao, Yanqing; Li, Haihua; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The inappropriate use of antibiotics has led to the emergence of multidrug-resistant strains. Bacteriophages (phages) have gained renewed attention as promising alternatives or supplements to antibiotics. In this study, a lytic avian pathogenic Escherichia coli (APEC) phage designated as PEC9 was isolated and purified from chicken farm feces samples. It was a member of the siphovirus-like by electron microscopy observation. Biological characterization revealed that it could lyse two serotypes of E. coli, including O1 (9/20) and O2 (6/20). The optimal multiplicity of infection (MOI) of phage PEC9 was 0.1. Phage PEC9 had a latent period of 20 min and a burst period of 40 min, with an average burst size of 68 plaque-forming units (PFUs)/cell. It maintained good lytic activity at pH 3-11 and 4-50 ℃ and could efficiently inhibit the bacterial planktonic cell growth and biofilm formation, and reduce bacterial counts within the biofilm, when the MOI was 0.01, 0.1, and 1, respectively. Whole-genome sequencing showed that PEC9 was a dsDNA virus with a genome of 44379 bp and GC content of 54.39%. The genome contains 56 putative ORFs and no toxin, virulence, or resistance-related genes were detected. Phylogenetic tree analysis showed that PEC9 is closely related to E. coli phages vB_EcoS_Zar3M, vB_EcoS_PTXU06, SECphi18, ZCEC10, and ZCEC11, but most of these phages exhibit different gene arrangement. Subsequently, the therapeutic effects of the phages were investigated in the mice model. The results showed that phage PEC9 could successfully protect mice against APEC infection, including improved survival rate, reduced bacterial loads, and organ lesions. To conclude, our results suggest that phage PEC9 may be a promising candidate that can be used as an alternative to antibiotics in the control of APEC infection.